Clinical outcomes of patients with corticosteroid refractory immune checkpoint inhibitor-induced enterocolitis treated with infliximab. Issue 7 (7th July 2021) - Alexander, James L; Ibraheim, Hajir; Sheth, Bhavisha; Little, Jessica; Khan, Muhammad Saheb; Richards, Camellia; Hunter, Nikki; Chauhan, Dharmisha; Ratnakumaran, Raguprakash; McHugh, Kathleen; Pinato, David J; Nathan, Paul; et al.
Abstract : Introduction: Immune checkpoint inhibitors (CPIs) have changed the treatment landscape for many cancers, but also cause severe inflammatory side effects including enterocolitis. CPI-induced enterocolitis is treated empirically with corticosteroids, and infliximab (IFX) is used in corticosteroid-refractory cases. However, robust outcome data for these patients are scarce. Methods: We conducted a multicenter (six cancer centers), cohort study of outcomes in patients treated with IFX for corticosteroid-refractory CPI-induced enterocolitis between 2007 and 2020. The primary outcome was corticosteroid-free clinical remission (CFCR) with Common Terminology Criteria for Adverse Events (CTCAE) grade 0 for diarrhea at 12 weeks after IFX initiation. We also assessed cancer outcomes at 1 year using RECIST V1.1 criteria. Results: 127 patients (73 male; median age 59 years) were treated with IFX for corticosteroid-refractory CPI-induced enterocolitis. Ninety-six (75.6%) patients had diarrhea CTCAE grade >2 and 115 (90.6%) required hospitalization for colitis. CFCR was 41.2% at 12 weeks and 50.9% at 26 weeks. In multivariable logistic regression, IFX-resistant enterocolitis was associated with rectal bleeding (OR 0.19; 95% CI 0.04 to 0.80; p=0.03) and absence of colonic crypt abscesses (OR 2.16; 95% CI 1.13 to 8.05; p=0.03). Cancer non-progression was significantly more common in patients with IFX-resistant enterocolitis (64.4%) as compared with patients with IFX-responsive enterocolitis (37.5%; p=0.013). Conclusion: This is the largest study to date reporting outcomes of IFX therapy in patients with corticosteroid-refractory CPI-induced enterocolitis. Using predefined robust endpoints, we have demonstrated that fewer than half of patients achieved CFCR. Our data also indicate that cancer outcomes may be better in patients developing prolonged and severe inflammatory side effects of CPI therapy.